Cumulative socioeconomic status and incident type 2 diabetes among African American adults from the Jackson heart study - LáShauntá M. Glover; Chantel L. Martin; Annie Green-Howard; Reuben Adatorwovor; Laura Loehr; Brooke Staley-Salil; Kari E. North; Mario Sims (SSM: Population Health, 2023)
Background: The cumulative socioeconomic status (SES) model posits that childhood and adult experiences accumulate to influence disease risk. While individual SES indicators such as education and income are independently associated with incident type 2 diabetes (T2D), the association of cumulative SES and incident T2D is unclear, especially in African American adults. Methods: We utilized cohort data of African American participants (n = 3681, mean age 52.6 years) enrolled in the Jackson Heart Study from 2000 to 2013 free of T2D or cardiovascular disease at baseline (2000–2004). Cumulative SES scores at baseline were derived using six SES indicators (education, wealth, income, occupation, employment status, and mother's education) categorized as low, middle, and high. Incident T2D was defined at exam 2 (2005–2008) or exam 3 (2009–2013) based on fasting glucose ≥126 mg/dL, HbA1c ≥ 6.5, reported diabetic medication use, or self-reported physician diagnosis. Proportional hazards regression, allowing for interval censoring, was used to estimate the association between cumulative SES and incident T2D (hazard ratio(HR), 95% confidence interval (CI)) after adjustment for covariates. Sex and age differences were tested using interaction terms. Results: There were 544 incident T2D cases. The association between low (versus high) cumulative SES and incident T2D was not significant (HR 1.04 [95% CI 0.85, 1.28]) and did not differ by sex (p value for interaction>0.05). However, there were differences by (age p value for interaction = 0.0052 for middle-aged adults and 0.0186 for older adults). Low (versus high) cumulative SES was associated a greater hazard of incident T2D among those 20–46 years (HR 1.12 [95% CI 1.03, 1.21]), 47–59 years (HR 1.25 [95% CI 1.06, 1.47]) and those 60–93 years (HR 1.39 [95% CI 1.09, 1.78]) after adjustment for sex and family history of diabetes. Associations attenuated after adding behavioral and lifestyle risk factors. Conclusion: The association of low cumulative SES and incident T2D differed by age, which may suggest interventionist should consider impacts of SES on T2D by age.